Pituitary tumors: Cell type-specific roles for BMP-4 - Labeur, Marta (2010)
BMP-4 plays a crucial role not only in the formation of the anterior pituitary during embryo development but also in the pathogenesis of pituitary tumors in adults. In tumor cells, BMP-4 promotes prolactin secretion and lactotroph cell proliferation through a Smad-estrogen receptor crosstalk but it inhibits ACTH production and cell proliferation of corticotrophs. In addition, BMP-4 increases GH secretion in rat pituitary tumor somatolactotroph GH3 cells and FSHβ subunit gene transcription in the murine gonadotroph cell line, LβT2. Therefore, BMP-4 has a differential role on different types of pituitary tumors: it promotes pituitary prolactinoma while it inhibits corticotroph pathogenesis in Cushing's disease. The modulation of BMP-4 also plays an important role in the therapeutic mechanism of action of bromocriptine, somatostatin analogs and retinoic acid.